2017
DOI: 10.21511/imfi.14(4).2017.05
|View full text |Cite
|
Sign up to set email alerts
|

Tax control of transfer pricing

Abstract: The subject of the scientific work is analysis of the essence of the "transfer pricing" concept. It has been proven that transfer pricing is an economic and legal tool used by business entities for their tax burden optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…A similar conclusion is reached by MELNYCHENKO, PUGACHEVSKA and KASIANOK (2017), who argue that the transfer price generated by a multinational company between two units is an economic and legal tool used to optimize the tax burden. LOHSe and RIEDEL (2013) published results of a study assessing the impact of transfer pricing rules on the behavior of multinational companies in intra-group price distortions, where the authors argue that the introduction of certain transfer pricing rules increases the profits that are reflected in the profitability of businesses in high tax jurisdictions, and reduce them in low tax jurisdictions.…”
Section: Literature Reviewsupporting
confidence: 63%
See 1 more Smart Citation
“…A similar conclusion is reached by MELNYCHENKO, PUGACHEVSKA and KASIANOK (2017), who argue that the transfer price generated by a multinational company between two units is an economic and legal tool used to optimize the tax burden. LOHSe and RIEDEL (2013) published results of a study assessing the impact of transfer pricing rules on the behavior of multinational companies in intra-group price distortions, where the authors argue that the introduction of certain transfer pricing rules increases the profits that are reflected in the profitability of businesses in high tax jurisdictions, and reduce them in low tax jurisdictions.…”
Section: Literature Reviewsupporting
confidence: 63%
“…Many foreign publications deal with the issues of avoiding taxation through offshore territories by means of transfer pricing mechanisms. The question of transfer pricing control and management in the context of tax optimization was investigated by DEVEREUX and MAFFINI (2007), LOHSE and RIEDEL (2013), MARQUES and PINHO (2015), RUF AND WEICHENRIEDER (2015), HUDA, NUGRAHENI and KAMARUDIN (2017), MELNYCHENKO, PUGACHEVSKA andKASIANOK (2017) PRETTL (2018), BEEBEEJAUN (2019), CLIFFORD (2019), HIRA, MURATA and MONSON (2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some jurisdictions, companies that manipulate transfer pricing to shift profits may lose access to tax incentives, deductions, and benefits that are intended to promote legitimate business activities and economic growth (Melnychenko, Pugachevska, Kasianok, 2017).…”
Section: Loss Of Benefits and Incentivesmentioning
confidence: 99%
“…The affiliates tend to collude instead of competing in their profit generation endeavours as well as in their pricing decisions, thereby over or under-invoicing to reduce the tax burden or avoid it in some countries through "profit maximising transfer pricing" (Reuter, 2012, p. 213). Melnychenko, Pugachevska and Kasianok (2017) while focusing on TP in Ukraine, concluded that TP was not merely exploited through tax planning to achieve tax avoidance, but it can be used for outright tax evasion. The researchers highlighted three scenarios of outright tax evasion: (1) the use of fictitious or "pseudo imports" and these imports are at higher prices and exports at lower prices (2) the generation of baseless value added tax (VAT) credits and illegal VAT offset and evasion using "pseudo or non-typical exports" and pricing them highly (3) the use of fictitious companies.…”
Section: Income Shifting Through Under or Over-invoicingmentioning
confidence: 99%